Where is the green sheep? - Fox, Mem, 1946-; Horacek, Judy (Orlando : Harcourt, 2004)
A story about many different sheep, and one that seems to be missing.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
1.7
K-3.
K-3
Keywords: Sheep -- Juvenile fiction; Sheep -- Fiction; Stories in rhyme; Sheep -- Fiction; Stories in rhyme